Henriette-Rika Benveniste, Λούνα: Δοκίμιο ιστορικής βιογραφίας [Luna: an essay in historical biography] - Kavala, Maria (Historein, 2019)
Review of Henriette-Rika Benveniste. Λούνα: Δοκίμιο ιστορικής βιογραφίας [Luna: an essay in historical biography]. Athens: Polis, 2017. 222 pp.